A seed germination-inspired interface polarization augmentation strategy toward superior electromagnetic absorption performance. (October 2022) - Jia, Zirui; Liu, Xuehua; Zhou, Xinfeng; Zhou, Zehua; Wu, Guanglei
Abstract: Dielectric/magnetic composites are considered as attractive candidates for high-performance electromagnetic wave absorption (EMA) materials. However, the agglomeration of magnetic nanoparticles (NPs) in the carbon matrix is an unavoidable problem. The homogeneous interfaces caused by magnetic agglomeration are often detrimental to the reinforcement of interfacial polarization. Herein, inspired by seed germination process, a high temperature derived carbon nanotube method was employed to prevent the agglomeration issue of magnetic NiCo alloy NPs. With the significant proliferation of heterogeneous interfaces due to the separation between NiCo alloy NPs, the interfacial polarization is significantly reinforced. Besides, the graphitized carbon obtained by high temperature carbonization is responsible for the conductive loss. As a consequence, the NiCo alloy@N doping carbon nanosheets (NiCo@NCS) composites illustrated a strong EM attenuation ability compared to the composites with magnetic NiCo alloy NPs agglomeration. Finally, the minimum reflection loss ( RL min ) was −61.4 dB and widest absorption bandwidth ( f max ) reached 4.72 GHz at 2.0 mm and 2.1 mm, respectively. This seed germination-inspired approach can be a significant and efficient reference to prevent the agglomeration of magnetic NPs in dielectric/magnetic composites. Graphical abstract: Inspired by seed germination process, a high temperature derived carbon nanotube method was employed to prevent the agglomeration issue of magnetic NiCo alloy NPs for enhanced electromagnetic wave absorption performance. Image 1 Highlights: A method was employed to prevent the magnetic agglomeration NiCo alloy NPs inspired by seed germination process. The heterogeneous interface increased significantly due to the detachment of magnetic particles from the nanosheets. The heterogeneous interfacial polarization and conductive loss dominated the EM loss mechanism.